Dekontstruksi Narasi dan Otoritas dalam Tafsir Klasik (Analisis Hermeneutis terhadap Metodologi Imam at-Tabari pada Kisah Nabi Sulaiman Surah Sad Ayat 34) - Mubarok, Akhmad Luthfi (Green Publisher Indonesia, 2025)
Qur'anic exegesis is often enriched with Isra'aliyyat narrations to supplement its concise narratives. Imam al-?abari, in his magnum opus Jami? al-Bayan, includes many such reports, one of which concerns the trial of Prophet Solomon (Sulayman) in Surah ?ad, verse 34. This research transcends the traditional criticism of these Isra'iliyyat. Employing a critical hermeneutic framework that combines a 'hermeneutics of suspicion' with a 'hermeneutics of retrieval,' this article posits that al-Tabari's inclusion of problematic narrations was not a methodological weakness but a conscious intellectual act. Al-Tabari deliberately bequeathed a hermeneutic tension between the preservation of the transmission-based tradition (naql) and the safeguarding of theological integrity ('aql). Through a comparative analysis with later exegetes (such as Ibn Kathir and al-Razi) and an interdisciplinary analysis of literary motifs, this study demonstrates that the case of Surah Sad: 34 serves as a microcosm reflecting the complex dynamics in the formation of authority and discourse in classical Islamic exegesis (tafsir). Consequently, al-Tabari is viewed not merely as a collector, but as a brilliant archivist who mapped the entire spectrum of thought of his time, leaving it to be interrogated by subsequent generations.